Albumin-to-globulin ratio as an independent predictor of mortality in chronic heart failure. (5th June 2018) - Niedziela, Jacek T; Hudzik, Bartosz; Szygula-Jurkiewicz, Bozena; Nowak, Jolanta U; Polonski, Lech; Gasior, Mariusz; Rozentryt, Piotr
Aim: Albumin-to-globulin ratio (AGR) is emerged as a marker of impaired prognosis. We determined the predictive value of AGR in patients with heart failure with reduced ejection fraction (HFrEF).Methodology: 999 patients with HFrEF were enrolled. Rates of 1-year all-cause mortality were compared between AGR quartiles (Q). Moreover, multivariate survival analysis in Cox's regression model and receiver operating characteristic analyses were performed.Results: 90-day and 1-year mortality was the highest in AGR Q1. AGR was an independent predictor of 90-day and 1-year mortality. Receiver operating characteristic analysis revealed moderate diagnostic value in predicting 90-day (AGR cutoff <1.2) and 1-year (AGR cutoff <1.38) mortality.Conclusion: AGR had a good prognostic value and remained an independent predictor of mortality in HFrEF patients.